C) It doesn’t satisfy either the top or bottom equations.
When we plug them into the top equation:
![- 3 + 4( - 5) = - 15](https://img.qammunity.org/2019/formulas/mathematics/middle-school/9hjrsgd0t8aqnofykkbuu0owfso8wee26o.png)
Simplify:
![- 3 + ( - 20) = - 15 \\ \\ - 23= - 15](https://img.qammunity.org/2019/formulas/mathematics/middle-school/w82fv1rdsgvnho3lv640q9sqyco6tqqy2g.png)
Because the statement of -23 = -15 is wrong, the solution pair is wrong for the top equation.
When we plug them into the bottom equation:
![- 2(3) - 3( - 5) = - 8](https://img.qammunity.org/2019/formulas/mathematics/middle-school/9wjafkmh2ser377tj1z8r94kgnvivdtduy.png)
Simplify:
![- 6 - ( - 15) = - 8 \\ \\ 9 = - 8](https://img.qammunity.org/2019/formulas/mathematics/middle-school/nz7w0yjr09qer27ltumb5120icgozzt94v.png)
9 = -8 is not a valid statement, so the pair doesn't satisfy both of the equations.